Physical and Chemical Properties of Indonesian Coffee Beans for Different Postharvest Processing Methods - Elin Yusibani; Peter Lloyd Woodfield; Adi Rahwanto; Muhammad Syukri Surbakti; Rajibussalim Rajibussalim; Rahmi Rahmi (Directorate for Research and Community Services, Institut Teknologi Bandung, 2023)
The purpose of this study was to identify the physical and chemical properties of Indonesian coffee beans for different postharvesting methods after being roasted. Several types of Indonesian export coffee, i.e., Gayo Luwak coffee, Wamena coffee, Toraja coffee, Gayo coffee, Flores coffee and Kintamani coffee, were used in the present study. Each coffee has its own aroma and taste according to the location, soil type, and land elevation. The roasting process started with preheating the roasting machine, after which the samples were roasted for about 15 minutes at 215℃ to obtain the medium-to-dark (MTD) roasting level. The physical properties measured included density, mass loss, porosity, water content, and morphology using a scanning electron microscope. The transmittance spectrum was observed by Fourier transform infrared spectroscopy (FTIR). The physical properties of the coffee were successfully measured. The bulk density varied from 0.6 to 0.7 g/cm3, and particle density was about 0.9 g/cm3 for green beans. The roasting process reduced the bulk and particle density to 0.3 g/cm3 on average and 0.8 g/cm3, respectively. The fully-washed condition gave an overlapping spectrum for green and roasted beans, which shows that the roasting process did not affect the spectrum. The results can be used to study the coffee quality resulting from different postharvest processing methods.